Mutations in the HvMKK3 and HvAlaAT1 genes affect barley preharvest sprouting and after‐ripened seed dormancy. Issue 4 (10th June 2020) - Vetch, Justin M.; Walling, Jason G.; Sherman, Jamie; Martin, John M.; Giroux, Michael J.
Abstract: Preharvest sprouting (PHS) is a natural phenomenon that negatively impacts various crops across the globe when late‐season rainfall causes seeds to germinate prior to harvest. Prevention of PHS in small grains such as barley ( Hordeum vulgare L.) and wheat ( Triticum aestivum L.) is of particular importance because of the large acreage devoted to them. Barley is the fourth most grown cereal crop and is often susceptible to PHS damage, which limits the regions in which barley can be grown without heavy losses. Preharvest sprouting damage could be mitigated by incorporation of genetic alleles that impart desired levels of dormancy at specific times in grain maturity, ideally high dormancy at harvest with a fast loss of dormancy upon after‐ripening. Toward this goal, 114 barley varieties were assessed for dormancy at physiological maturity and in after‐ripened grains. Three genes previously associated with dormancy in barley or wheat ( HvAlaAT1, HvMKK3, and HvMFT ) were sequenced from all lines and assessed for allelic diversity. The resulting alleles were assessed for association with dormancy at each of the maturity time points. In total, seven missense mutations were discovered across the three genes. It was observed that a single missense mutation in HvAlaAT1 (L214F) is associated with loss of dormancy in after‐ripened grain, while a single missense mutation in HvMKK3 (E165Q) is associated with a large loss of dormancy starting around physiological maturity. This study suggests that different genes may be associated with dormancy at different time points in grain maturity, which would allow for selective breeding of specific dormancy time periods.